Sah atau Tidak Smart Contract Dalam Sistem Blockchain? - Suwardiyati, Rumi; Widhiyanti, Hanif Nur; Wicaksono, Setiawan (Widya Yuridika, 2024)
Smart contracts in blockchain systems are widely used as automated agreements that can expedite the execution of a contract. Based on the characteristics of smart contracts analyzed through agreements in the Indonesian Civil Code (BW), it can be concluded that smart contracts can be legally used in contractual legal activities in Indonesia. This is because smart contracts meet the requirements outlined in the BW as guidelines for contract formation, particularly concerning the validity of contracts. Using a normative method, which employs literature as legal material for this writing, the result shows that the validity of smart contracts in blockchain, based on Indonesian contract law, aligns with the contract law that fulfills the requirements of Article 1320 BW. Smart contracts can also be classified as standard agreements where the parties agree based on an existing and mutually agreed-upon contract. Until now, there are no specific regulations regarding smart contracts in Indonesia, even though smart contracts are already widely used in the country.